2020
DOI: 10.1155/2020/6146104
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence and Biodegradation Characteristics of Benzoic Acid-Degrading Bacterium Pseudomonas sp. SCB32

Abstract: Allelochemicals are metabolites produced by living organisms that have a detrimental effect on other species when released into the environment. These chemicals play critical roles in the problems associated with crop replanting. Benzoic acid is a representative allelochemical found in root exudates and rhizosphere soil of crops and inhibits crop growth. The bioremediation of allelochemicals by microorganisms is an efficient decontamination process. In this research, a bacterial strain capable of degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…The great phenotypic difference shown by the isolated samples and the presence of other closely related species may lead to differences in the diagnosis of this type of bacteria when using traditional and molecular methods 35 . According to numerous studies about the identification of these bacteria 36,37 , our findings supported the integration of morphological features with biochemical characteristics and the genetic sequence of the 16S rRNA gene, confirming the diagnosis of the bacteria isolated from the soil as belonging to the genus Pseudomonas. This outcome is in line with what Eremwanarue et.…”
Section: Identification Of Pseudomonas Aeruginosasupporting
confidence: 80%
“…The great phenotypic difference shown by the isolated samples and the presence of other closely related species may lead to differences in the diagnosis of this type of bacteria when using traditional and molecular methods 35 . According to numerous studies about the identification of these bacteria 36,37 , our findings supported the integration of morphological features with biochemical characteristics and the genetic sequence of the 16S rRNA gene, confirming the diagnosis of the bacteria isolated from the soil as belonging to the genus Pseudomonas. This outcome is in line with what Eremwanarue et.…”
Section: Identification Of Pseudomonas Aeruginosasupporting
confidence: 80%
“…The crop can be grown continuously on the same land for years when the inhibitory chemicals are removed. ( Gao and Wen, 2016 ; Xiang et al., 2020 ). Therefore, it is very important to understand the compositions of these inhibitory chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in this study that the lowest dibenzofuran concentration (15 ppm) had shown the best concentration for maximum bacterial degradation of dibenzofuran in landfill leachate. Substrate availability represents the carbon sources the bacterial community uses to proliferate (Xiang et al, 2020). Lower substrate concentration might cause disability of the bacteria to proliferate, while in higher substrate concentration, accumulation of the by-products might inhibit bacterial growth to the extent that it is toxic to the bacteria cells (Maier & Pepper, 2015).…”
Section: Optimization Of Dibenzofurans Biodegradationmentioning
confidence: 99%